2021
DOI: 10.21608/ejchem.2021.73861.3652
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Determination and Study Toxicity Effects of new Mixed ligands Complexes Derivative from 8- Hydroxy Quinoline with Pd(II)

Abstract: This academic research consists of mixed ligands 8-hydroxy quinolone and new azo ligand [ (E)-2-((4-methoxyphenyl) diazenyl)-4-methyl-1H-imidazole](PMI) both of them coordinated with (Cu ,Ni and Pd)(II) , the mole ratio was (1:1:1) . the suggestion geometrical structures of mixed ligands and its complexes have been studied by (FT.IR, UV-Visible, 1H-NMR, Mass and elementary analysis (C.H.N) ) In addition, an electrical molar conductivity and magnetic susceptibility used for complexes . The results of analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The absence of new band around 526 and 441 cm -1 due to metal nitrogen and oxygen respectively in reagent spectrum and which appearance in complex spectrum. [26][27][28][29][30] Table…”
Section: Infrared Spectrummentioning
confidence: 99%
“…The absence of new band around 526 and 441 cm -1 due to metal nitrogen and oxygen respectively in reagent spectrum and which appearance in complex spectrum. [26][27][28][29][30] Table…”
Section: Infrared Spectrummentioning
confidence: 99%
“…This study focused on the cytotoxic effect of Pd(II) complex on Thyroid cancer cells line (FTC-133) compared with healthy cells line (WRL-68) by taking number of concentrations of Pd(II) complex (6.2-400) µg/ml and adding these concentrations to both cancer and healthy cells by using MTT method [15] , the result is shown that (25)µg/ml of Pd(II) complex is the best concentration to inhibit the tumor of cancer cells . However, it was less influence on healthy cells , which is approved that Pd(II) complex might be used as new medicine of Thyroid cancer line (FTC-133).…”
Section: Cytotoxic Activity Of [Pd(hl) 2 ]mentioning
confidence: 99%